Seguna, Paul: my Naval Reserve experience (March 12, 2019) - Yaroslavsky, Misha; Seguna, Paul (2019)
ABSTRACT: Lieutenant Commander Paul Seguna served in the Canadian Armed Forces from 1974 to 2017. His service is marked by a great deal of transformative career changes that allowed him to gain a broad perspective of the Canadian Armed Forces. It began in the Naval Reserve as one of the first Naval Reserve radar plotters in 1975, after becoming one of the first graduates in the Halifax Naval Reserve training base. Following that, he had many adventures, the most memorable trip to him being his trip to Russia in 1976 on the HMCS Athabasca. After becoming a Petty Officer Second Class in 1982, Lieutenant Commander Seguna was swayed by military life, and decided to join full time. He worked as a liaison officer until 1992, where he then transferred to public affairs. He served as a reservist until 2002, until he rejoined as a fully commissioned officer in public affairs up to his retirement in 2017. The major findings in his story are his experiences as a non-commissioned radar plotter, as well as his extensive experience in the military. The interview details how he charted points on the map, at a time when electronic devices were unavailable. He explains in detail about all the ships in which he served. In addition, Lieutenant Commander Seguna was shares the differences and similarities between being a reservist and a full time officer. 0:00 – 1:05 Immigrated to Vancouver in 1974 from Sidney Australia, then joined the Naval Reserve. 1:05 – 7:50 Joined Summer training program for high school students interested in the Naval Reserve. 7:50 – 9:20 Difference between regular force and reserve. 14:00 – 15:00 Different roles in Naval Reserve and discussion on gate vessels. 15:00 – 17:45 Role of the radar plotter. 20:30 – 21:22 Different classes of service in the naval reserve. 56:00 – 1:10:07 Enters Russia for HMCS Athabasca trip. 1:25:23 – 1:52:13 Switch to regular force and career in public affairs. 1:52:21 – 2:15:16 Improvements and changes in the Naval Reserve; An interview/narrative of Paul Seguna's experiences serving in the Naval Reserves. Interview took place on March 12, 2019 in Victoria, B.C.; Rank: Lieutenant-Commander. ; Interviewee: Seguna, Paul; Interviewer: Yaroslavsky, Misha